Evaluasi Tarif Rawat Inap menggunakan Metode Activity Based Costing pada Rumah Sakit Umum Daerah Prof. Dr. W. Z. Johannes Kupang (Lembaga Pengembangan Kinerja Dosen, 2025)
Accurate inpatient tariff determination is essential for ensuring efficiency and cost fairness in hospitals. This study aims to compare inpatient tariffs at RSUD Prof. Dr. W. Z. Johannes Kupang using the Activity-Based Costing (ABC) method and the traditional unit cost method. The research adopts a descriptive-evaluative approach, with data collected through observation, interviews, and documentation. The ABC method allocates costs based on the activities consumed by each inpatient class, resulting in more accurate cost calculations. The findings show that tariffs calculated using the ABC method are lower than those of the traditional method across all classes—for example, the VIP class costs Rp715,359 (ABC) compared to Rp750,000 (traditional). This difference indicates that the traditional method does not proportionally reflect cost allocation. Therefore, the ABC method is recommended as an alternative approach to improve the accuracy of hospital service tariff setting.